Sol-Gel Synthesis of ZrO2 Coatings on Micro End Mills - Morrow, Justin; Tejedor-Anderson, M. Isabel; Anderson, Mark A.; Ruotolo, Luis A.; Pfeffernkorn, Frank (8th International Conference on MicroManufacturing (ICOMM 2013), 2013)
The objective of this paper is to develop a coating method for placing ultra-thin zirconia films, fabricated using sol-gel methods, onto micro end mills for purposes of improving performance with respect to tool wear and cutting forces. Sol-gel synthesis is investigated because of its potential as a low energy and inexpensive method for depositing a variety of wear resistant and chemically stable oxide coatings that could potentially reduce forces and extend tool life. Two sol-gel based deposition methods are investigated: dip-coating and electrophoresis. The coatings are deposited on 300-?m-diameter micro end mills, sintered, and tested while cutting 6061-T6 aluminum. Initial results suggest that sol-gel coating methods can produce the required coverage and conformity in the cutting zone. However, preliminary findings show that the coating is removed in the cutting zone after a short time of machining (6 sec). The tool pre-treatment and extent of sintering, which affect surface adhesion require further study and optimization.
Keywords: Sol-Gel; Micro End Milling; Zirconia; Coating